CLUSTERIZATION OF SLOBOZHANSCHINA’S EDUCATIONAL SPACE BY CREATION AND FUNCTIONING KHARKIV UNIVERSITY CONSORTIUM - Byelova , L. (Pressing Problems of Public Administration, 2020)
Based on the analysis of the content of the Paris Communiqué, the Bologna Declaration, the Strategy of reforming higher education of Ukraine until 2020, it is concluded that they are united by the idea of enhancing academic freedom of higher education and introducing the principles of integrity in the educational process, building institutional autonomy of higher education institutions and institutions of higher education. Employees in governing higher education and developing the social responsibility of educators for the course of socio-political transformations. The historical experience of the creation and operation of innovative educational clusters (EdClusters), whose active policy of implementation began in European countries in the early 1990s, is analyzed. Practical experience of creation and functioning in the Slobozhanshchina of such innovative educational cluster as Kharkiv University Consortium (UniCon) is presented. The main purpose of its activity is cooperation, combination of information, personnel and financial resources for achievement of scientifically grounded social effect in the field of academic mobility, academic research development and innovation, improvement and improvement of quality, etc. The article concludes that today significant transformations are taking place not only in the public consciousness, but also in all spheres of public life in Ukraine. Recent innovations, which were initiated with the implementation of the Law of Ukraine “On Higher Education” and “On Education”, are already beginning to change the nature of relations in the scientific environment, making it more competitive and thus more focused on the end user of educational services. . The standard of higher education is changing, independent centers for assessing the quality of higher education are emerging, fields of knowledge and scientific specialties are being transformed. It is very gratifying that we are following the mainstream of presidential reforms, setting and solving the most pressing problems of the development of modern Ukrainian society. Prospects for further research in this direction can be considered the development of the Development Strategy of the Kharkiv University Consortium in the context of reforming the higher education system at the regional level.